THE INFLUENCE OF SOCIAL MEDIA MARKETING CONTENT ON THE PURCHASE DECISION OF WARDAH LOCAL BEAUTY PRODUCTS AMONG GENERATION Z IN SOUTH JAKARTA (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to determine the influence of Instagram social media marketing content on the purchasing decisions of Wardah local beauty products among Generation Z in South Jakarta. This study used a quantitative method by distributing questionnaires to 100 respondents and analyzing them using SPSS version 26. The results showed that Instagram social media marketing content significantly influenced Wardah purchasing decisions among Generation Z in South Jakarta, with a coefficient of determination of 50.3%. This indicates that engaging, interactive, and trend-following Instagram content can influence consumer purchasing decisions.